Skin Rejuvenation with Microbotox: A Review - Malinda, Ifen Ayu; Jusuf, Nelva Karmila (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Skin aging is characterized by a gradual loss of tissue and organ function. Skin aging can be classified into two types: intrinsic aging, associated with the aging process itself, and extrinsic aging, which is linked to external factors. Microbotox—an intradermal injection of diluted botulinum toxin—has emerged as a promising technique for rejuvenation by improving skin texture, pore size, and sebum control. This review aims to provide a comprehensive overview of the microbotox technique in the context of skin aging, emphasizing its mechanisms, indications, and clinical outcomes. Discussion: In Asia, intradermal injection of botulinum toxin or microbotox has been widely adopted. The technique involves injecting microdroplets of onabotulinumtoxin type A (ONA) into the intradermal layer at lower concentrations compared to conventional methods. Microbotox is highly sought after for its ability to improve skin texture, address enlarged pores, control sebum, and rejuvenate the skin without the stiffness often associated with conventional botox. Conclusion: Microbotox provides multiple dermatological benefits, including improved skin texture, pore reduction, oil control, and fine line softening, with minimal side effects. As an intradermal technique, it offers a safer and subtler alternative to traditional botox. It provides rapid results lasting up to 3-4 months, making it a valuable tool in aesthetic dermatology. This has made microbotox one of the most popular skin rejuvenation treatments today.